Forms of Freedoms: Marie Darrieussecq, Catherine Malabou, and the Plasticity of Science - Dalton, Benjamin (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2020)
This article brings the writing of Marie Darrieussecq into dialogue with the philosophy of Catherine Malabou, exploring how both think the mutability and transformability of the body in relation to recent scientific and technological discovery and innovation. From the metamorphosis of a woman into a sow in Truismes (1996) to the cloning of human life in Notre vie dans les forêts (2017), Darrieussecq’s novels foreground the body as a site of constant change and reinvention. Meanwhile, Malabou’s interdisciplinary elaboration of the concept of ‘plasticity’ between continental thought and the biological sciences reveals all structures and forms of life to be plastic and intrinsically open to change, from the neuroplasticity of the human brain to the epigenetic development of organisms. This article presents both Darrieussecq and Malabou as writers and thinkers of plasticity, exploring how their respective plasticities develop through a relationship to science which is itself changeable and ambiguous. In different but converging ways, both suggest how science discovers and innovates with the plasticity of life, whilst often also controlling and manipulating this same plasticity in the context of late capitalism. More optimistically, this article proposes that Darrieussecq and Malabou also envisage a becoming plastic of the sciences themselves, liberating plasticity as a discourse of freedom as a thinking with science, literature, and philosophy.